Produção de concreto utilizando cinzas das indústrias de cerâmica vermelha em substituição ao agregado miúdo - Silva, Allyson Leandro Bezerra (Universidade Federal Rural do Semi-Árido, 2017)
The growth of civil construction, a sector of great importance for the Brazilian economy, increases the extraction of raw materials, among them the extraction of sand from the river bed and consequent environmental damage. The use of ashes in partial replacement of the small aggregate used in concretes is not only seen as the use of a waste, but as a contribution to the economy and to the minimization of environmental impacts. In this way, the work analyzes the use of residual ash from furnaces of the red ceramic industry of the Vale do Assú region in the production of concrete for civil construction. In the tests were used the percentages of 0%, 10%, 20%, 30% and 40% of gray in the replacement of the small aggregate. The results of compressive strength of concrete specimens were submitted to analysis of variance and to the Tukey test at 5% of probability. Statistical analysis showed that with the replacement of 40% of sand by ash, concrete did not lose its characteristic resistance at 28 days. The resistance did not change, according to the statistic, with the increase of the substitutions. The compressive strength of the concrete was determined at 7 and 28 days and with the compressive strength tests the technical feasibility of the concrete with ash from the firewood burning of the ceramic industries was confirmed
Keywords: Areia; Resistência à compressão; Resíduo; Impacto Ambiental; Sustentabilidade; Sand; Compressive strength; Residue; Environmental impact; Sustainability; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO